(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1938)
The object was found in a pit in the course of tracing out the boundary wall of the prehistoric settlement which in turn was crossed by the wall of a Viking house. The ornamentation consists of a combination of chip-carving and interlacing work, together with an enrichment of geometrical patterns. It is conceivable that the mount was re-used as a brooch.